Mao: A Very Short Introduction - Davin, Delia (New York Oxford University Press, 2013)
"A giant of 20th century history, Mao Zedong played many roles: peasant revolutionary, patriotic leader against the Japanese occupation, Marxist theoretician, modernizer, and visionary despot. This Very Short Introduction chronicles Mao's journey from peasant child to ruler of the most populous nation on Earth. Delia Davin provides an invaluable portrait of Mao, showing him in all his complexity-ruthless, brutal, and ambitious, a man of enormous talent and perception, yet a leader who is still detested by some and venerated by others. She shows how he helped found both the Chinese Communist Party and the Red Army, and how for many years he fought on two fronts, for control of the Party and in an armed struggle for the Party's control of the country. His revolution unified China and began its rise to world power status. He was the architect of the Great Leap Forward that he hoped would make China both prosperous and egalitarian, but instead ended in economic disaster resulting in millions of deaths. It was Mao's growing suspicion of his fellow leaders that led him to launch the Cultural Revolution, and his last years were dogged by ill-health and his despairing attempts to find a successor. Davis also looks at the years of his death, when the reform leadership abandoned Mao's revolutionary goals and embraced the market."--Publisher's website. R
Includes Index and Illustrations.
Keywords: Mao, Zedong, -- 1893-1976.